Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Let us first substitute the value of x as -2 3(-2)² -2k(-2) +2m = 0 3(4) +4k + 2m = 0 12 +4k +2m = 0 4k +2m = -12 2k+m = -6------------------------(1)

Now, Let us substitute the value of x as 3 3(3)² -2k(3) +2m = 0 3*9 -6k +2m = 0 27 - 6k +2m = 0 -6k +2m = -27 6k-2m = 27------------------------------(2)

(1) * 2 ⇒ 4k+2m = -12 Now consider the second equation 6k-2m = 27 4k+2m = -12 10k = 15 ⇒ k = 15/10 ⇒ k = 3/2 , now substitute the value of k in equation (1) 2*3/2 +m = -6 3+m = -6 ⇒ m = -6-3 ⇒ m = -9. ∴ The value of k = 3/2 and the value of m = -9.

Thank you.....!!!! Mark as brainliest of helpful.. Yours, Jahnavi.